Microstructural, hardness, and wear properties of Mg2Si-reinforced Al matrix in-situ composites produced by low superheat casting - Ozkan, Tolga; Tutuk, Ibrahim; Acar, Serhat; Gecu, Ridvan; Guler, Kerem Altug (ELSEVIER, 2024)
In this study, Mg2Si-reinforced A356 and A413 aluminum matrix composites were fabricated by low superheat casting using AM50 magnesium alloy as a source for the in-situ formation of Mg2Si particles. AM50 was added to each Al alloy at 5 %, 10 %, and 15 % ratios, respectively. Casting temperatures for these composites were 650 degrees C for A356 and 620 degrees C for A413. After the production, the as-cast samples were reheated to 580 degrees C and quenched. The microstructure and hardness properties of both as-cast and reheated samples were investigated and wear tests were carried out on the as-cast specimens. As the AM50 ratio increased, the morphology of Mg2Si became finer, and polygonal primary particles were precipitated in the A356 and A413 matrix as-cast composites. The formation of in-situ Mg2Si particles improved the hardness of the composites by up to 47 %. The hardness values reached 94 and 93 HB in the A356-5 and A413-15 specimens, respectively. Besides, wear rates were decreased by up to 55 % in the Mg2Si-reinforced composites compared to the unreinforced alloys.
Keywords: Mg2Si; Al matrix composites; Low superheat casting; In -situ production; ALUMINUM-ALLOY; MECHANICAL-PROPERTIES; BEHAVIOR; A356; Materials Science